Reinforcing Effect of Nano Kaolin Clay on Some Optical Properties of Poly (methyl methacrylate) for Medical Application - Fouad. Sh. Hashim (Journal of Global Pharma Technology, 2018)
In this study, the effects of nano kaolin clay content on the optical properties of PMMA films are investigated. PVA solution used as a coated layer covered the nano-kaolin applied as filler. The reinforced nano-kaolin content of 1, 3, 5, and 7 wt%. Improve the absorbance of UV radiation for (PMMA/kaolin) nanocomposite films at 7 wt% allows use for protection purposes, such as solar radiation shield , in the manufacture of sunglasses to protect the human eye from UV radiation damaged to the tissues of the body and as packaging for storage drugs. The values of allowed and forbidden indirect transition optical energy gap decrease with increasing the rate of reinforced nano-kaolin up to (4.27, 3, 2.8, 2.49, 2.23 eV) and (3.99, 2.4, 2.1, 1.8, 1.3 eV) respectively. Refractive indexes, extinction coefficient of polymer reinforcement nano-kaolin were done.Key words: PMMA, Nano-kaolin clay, Optical properties, Composite materials.